Public Low-Cost Housing in Malaysia: Case Studies on PPR Low-Cost Flats in Kuala Lumpur - Goh, Ai Tee; Ahmad, Yahaya (Journal of Design and the Built Environment, 2011)
This paper examines the design quality of People's Housing Project (Program Perumahan Rakyat or PPR) low cost high rise flats developed by the National Housing Department (Jabatan Perumahan Negara or JPN) in Kuala Lumpur since the 1998. Quality Function Deployment method is used as a tool to analyze the current status and to prioritize the demanded quality from the selected PPR low-cost high rise flats' users. The study revealed that factors in determining a quality low-cost high-rise flat arranged in descending degrees of importance are house safety, provision of public amenities, unit internal environment, maintenance and surrounding environment, location, sanitary fittings, unit size, type of house, material used, unit internal layout, quality of workmanship, structure of the house and appearance. A Quality Chart for PPR low-cost high-rise flats in Kuala Lumpur was presented. Authority (47 per cent) has the highest relative degree of importance in determining the quality of PPR flats, followed by Design Element (34 per cent) and Quality of Living (19 per cent). Accordingly, the success of the schemes relies strongly on effective control and enforcement by the authorities. However, it can be improved by tackling on the Design Element (Architectural), whereby a revised typical unit layout plan and typical details have been proposed at the last section of the paper.